2018
DOI: 10.1073/pnas.1715915115
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the early cilia preassembly protein complex during motile ciliogenesis

Abstract: Motile cilia are characterized by dynein motor units, which preassemble in the cytoplasm before trafficking into the cilia. Proteins required for dynein preassembly were discovered by finding human mutations that result in absent ciliary motors, but little is known about their expression, function, or interactions. By monitoring ciliogenesis in primary airway epithelial cells and MCIDAS-regulated induced pluripotent stem cells, we uncovered two phases of expression of preassembly proteins. An early phase, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 69 publications
6
72
1
Order By: Relevance
“…On the other hand, preassembly genes such as DNAAF1, DNAAF3, DNAAF4, LRRC6, DNAAF6/PIH1D3/TWISTER/TWI, and DNAAF7/ZMYND10, were expressed at a later stage of cell differentiation, similar to dynein DNAI1 [65]. Based on these data, it can be assumed that R2SP is involved in the early phase of the formation of dynein arms when SPAG1 binds to DNAAF2.…”
Section: Composition Of R2sp Complex and Function In Dynein Arm Preasmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, preassembly genes such as DNAAF1, DNAAF3, DNAAF4, LRRC6, DNAAF6/PIH1D3/TWISTER/TWI, and DNAAF7/ZMYND10, were expressed at a later stage of cell differentiation, similar to dynein DNAI1 [65]. Based on these data, it can be assumed that R2SP is involved in the early phase of the formation of dynein arms when SPAG1 binds to DNAAF2.…”
Section: Composition Of R2sp Complex and Function In Dynein Arm Preasmentioning
confidence: 88%
“…SPAG1, like other proteins with TPR domains, (Table 1) mediates the delivery of clients from Hsp70 to Hsp90, thanks to simultaneous anchoring of the chaperones via EEVD residues within Hsp70 and Hsp90 C-terminal end to the designed TPR domains of SPAG1 [64]. SPAG1, besides RuvBL1, RuvBL2, and PIH1D2, interacts (possibly indirectly) with DNAAF5/HEATR2 (HEAT Repeat-Containing) and DNAAF2 (Table 1), and co-localizes with them in DynAPs [27,65]. Recent studies on ciliogenesis in human primary airway epithelial cells have shown that DNAAF5, SPAG1, and DNAAF2 undergo transcription during the early stages of airway epithelial cell differentiation.…”
Section: Composition Of R2sp Complex and Function In Dynein Arm Preasmentioning
confidence: 99%
See 1 more Smart Citation
“…Other PCD genes encoding cytoplasmic proteins that are associated with absence of ODA and IDA when mutated include: DNAAF1 (LRRC50, ODA7, MIM 613190) [90], LRRC6 (MIM 614930) [64,83], DNAAF5 (HEATR2; MIM 614864) [62], DNAAF3 (PF22; MIM 614566) [100], DNAAF4 (DYX1C1; MIM 608706) [145], SPAG1 (MIM 603395) [81], CCDC103 (MIM 614677) [121], ZMYND10 (MIM 607070) [102,155], CFAP298 (C21orf59; Kurly; MIM 615494)) [4], CFAP300 (C11orf70; MIM 618058)) [59] and PIH1D3; MIM 300933) [112,119] (Table 1). The exact function of these proteins is not known, but evidence points to close interactions among several proteins, as well as protein complexes and heat-shock proteins suggesting that they may function as chaperones during dynein arm protein assembly [65,92], e.g., LRRC6 for instance interacts with ZMYND10 [155]; DNAAF5 interacts with SPAG1 and DNAAF2 during the earliest stages of cilia preassembly [65]; DNAAF2 interacts with DYX1C1 and PIH1D3 at later stages of cilia preassembly, possibly acting as linker proteins [65,119,145]. These proteins also interact with protein chaperones HSP70 and HSP90, facilitating the organization of dynein arm assembly [25,115,120,145].…”
Section: Genes Encoding Cytoplasmic Proteins Involved In Assemblymentioning
confidence: 99%
“…The most common genetic lesions that cause PCD are those that affect components of the ODA, including DNAH5, DNAI1, and DNAH11 (2)(3)(4). Another group of PCD associated genes encode ODA-docking complex components (CCDC114 and CCDC151) (5)(6)(7), or the proteins that play a role in the cytoplasmic assembly of dynein (SPAG1, DNAAF1-3, HEATR2, and DYX1C1) (8)(9)(10)(11)(12)(13)(14). In addition, mutations in two genes, CCNO (15) and MCIDAS (16), cause a PCD-like phenotype by greatly reducing the number of motile cilia.…”
Section: Introductionmentioning
confidence: 99%